STRENGTHENING WORK MOTIVATION, KNOWLEDGE SHARING, ORGANIZATIONAL SUPPORT, AND CREATIVITY TO IMPROVE TEACHER INNOVATION - Gita Kencanawaty; Soewarto Hardhienata; Herfina Herfina (Yayasan Education and Social Center, 2026)
This study aims to analyze the influence of work motivation, knowledge sharing, organizational support, and creativity on teacher innovation in public elementary schools in Tasikmalaya Regency. The research employed a mixed-method approach using the POP-SDM model, where research variables were initially explored qualitatively and subsequently tested quantitatively. The study involved 163 respondents drawn from 49 public elementary schools. Data were collected through questionnaires and supported by qualitative exploration to obtain a more comprehensive understanding of the relationships among variables. The data analysis techniques included descriptive statistical analysis and hypothesis testing using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings revealed that four direct effect hypotheses were accepted, indicating that several independent variables significantly influenced teacher innovation, while three direct hypotheses were rejected due to insignificant relationships. Furthermore, in the indirect effect analysis, one hypothesis was accepted and two were rejected, suggesting that not all mediating relationships were effective in explaining teacher innovation. The results highlight the importance of strengthening creativity, organizational support, and knowledge-sharing practices to improve teacher innovation in educational institutions. This study contributes to the development of human resource management and educational innovation strategies, particularly in enhancing teacher performance and innovation in elementary schools.